Technical report: the derivation and conversion of dimensional to nondimensional of mass balance equation and discretization using the explicit finite difference method / Intan Diyana Munir, Nur Nadzirah Sulaiman and Yang Nur Amalina Mohd Saad - Munir, Intan Diyana; Sulaiman, Nur Nadzirah; Mohd Saad, Nur Amalina (2017)
In this research, we focus on deriving a mathematical model of mass transfer equation proposed by Khalloufi et al. (2010) to a partial differential equations. Then the partial differential equations are converted to a nondimensional partial differential equations by substituting each nondimensionalized parameter into the derived partial differential equations. The nondimensional partial differential equations are discretized using the explicit finite difference method. The aim of our research is to derive the mathematical model and convert the derived model into a nondimensional equation then discretize it using the explicit finite difference method.